Unique continuation for fractional Schrödinger equations with rough potential - Rüland, Angkana (Arxiv, 2013)
This article deals with the weak and strong unique continuation principle for fractional Schr\"odinger equations with scaling-critical and rough potentials via Carleman estimates. Our methods allow to apply the results to variable coefficient versions of fractional Schr\"odinger equations.
Last revised 31 Oct 2013 (vs)
Gesehen am 27.05.2021